The pervasive crisis of diminishing radiation therapy access for vulnerable populations in the United States—part 3: Hispanic-American patients - Shearwood McClelland, III, MD; Carmen A. Perez, MD, PhD (Advances in Radiation Oncology, 2018)
Purpose: Health disparities have profoundly affected underrepresented minorities throughout the United States, particularly with regard to access to evidence-based interventions such as surgery or medication. The degree of disparity in access to radiation therapy (RT) for Hispanic-American patients with cancer has not been previously examined in an extensive manner. Methods and materials: An extensive literature search was performed using the PubMed database to examine studies investigating disparities in RT access for Hispanic-Americans. Results: A total of 34 studies were found, spanning 10 organ systems. Disparities in access to RT for Hispanic-Americans were most prominently studied in cancers of the breast (15 studies), prostate (4 studies), head and neck (4 studies), and gynecologic system (3 studies). Disparities in RT access for Hispanic-Americans were prevalent regardless of the organ system studied and were compounded by limited English proficiency and/or birth outside of the United States. A total of 26 of 34 studies (77%) involved analysis of a population-based database, such as Surveillance, Epidemiology and End Result (15 studies); Surveillance, Epidemiology and End Result-Medicare (4 studies); National Cancer Database (3 studies); or a state tumor registry (4 studies). Conclusions: Hispanic-Americans in the United States have diminished RT access compared with Caucasian patients but are less likely to experience concomitant disparities in mortality than other underrepresented minorities that experience similar disparities (ie, African-Americans). Hispanic-Americans who are born outside of the United States and/or have limited English proficiency may be more likely to experience substandard RT access. These results underscore the importance of finding nationwide solutions to address such inequalities that hinder Hispanic-Americans and other underrepresented minorities throughout the United States.